(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
When peaceful protests first began in Syria—particularly in the city of Daraa, the cradle of the Syrian revolution—during the wave of the Arab Spring, security analysts predicted that Syria would witness one of the most complex political and security developments in the region. Initially, the revolution was peaceful; however, after three years, it shifted toward armed resistance due to the involvement of various actors in the Syrian uprising. As a result, the Syrian revolution became significantly more violent compared to other Arab Spring uprisings, taking on sectarian and ethnic dimensions. The increasing violence led to the use of military aircraft, barrel bombs, and other weapons against protesters. In response, opposition groups also resorted to arms, fueled by regional and international support for the Syrian opposition. Consequently, the Syrian conflict evolved into a regional confrontation involving multiple states in the Middle East. Furthermore, the crisis was exacerbated by the entry of extremist groups from outside Syria, including the spread of al-Qaeda and factions of the Islamic State of Iraq and the Levant (ISIL/ISIS). What began as a political uprising demanding democratic transition and the removal of Bashar al-Assad ultimately transformed into a security, sectarian, and identity-based conflict. Thirteen years later, on January 8, 2024, the opposition forces managed to enter Damascus with the assistance of regional actors, most notably Turkey, which shares a strategic border with Syria.